2011
DOI: 10.1108/rjta-15-04-2011-b004
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Natural Dyeing Using Microwave Heating with Cochineal as Natural Dyes

Abstract: This research concerns making wool fabrics with dye extracted from cochineal using microwave heating. The result shows good fastness properties. To promote value addition in domestic processing and to boost rural income and employment in small-scale agroenterprises, it is necessary to promote non-polluting natural dyes, which involve inexpensive equipment and small-scale operations. The exploration of new flora can be environmentally and economically viable. Our aim is to show the feasibility of providing high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 7 publications
0
14
0
1
Order By: Relevance
“…Their main disadvantage lies in the order of magnitude of their extraction yield factors (a few grams of pigment per kilogram of dried raw material). To overcome this limitation, it has been suggested that other biological sources be exploited, such as fungi (both molds and yeasts), bacteria, algae, and plant cultures, since appropriate selection, mutation, or genetic engineering techniques are likely to significantly improve the pigment production yields with respect to wild organisms (Elshemy, 2011). Among the several pigment-producing microorganisms described in the literature, the fungus "Thermomyces" has been thoroughly studied (Palanivel and Vellingiri, 2009).…”
Section: Antimicrobial Finishesmentioning
confidence: 98%
“…Their main disadvantage lies in the order of magnitude of their extraction yield factors (a few grams of pigment per kilogram of dried raw material). To overcome this limitation, it has been suggested that other biological sources be exploited, such as fungi (both molds and yeasts), bacteria, algae, and plant cultures, since appropriate selection, mutation, or genetic engineering techniques are likely to significantly improve the pigment production yields with respect to wild organisms (Elshemy, 2011). Among the several pigment-producing microorganisms described in the literature, the fungus "Thermomyces" has been thoroughly studied (Palanivel and Vellingiri, 2009).…”
Section: Antimicrobial Finishesmentioning
confidence: 98%
“…Many researchers deliberated some new techniques and methods for saving time, water as well as energy [16,17] . Microwave irradiation, has been confirmed to be more rapid, uniform, efficient, and it can be used as alternative to conventional heating source [18,19] . Microwave irradiation can implement easily inside the fabric's particles, can be heated simultaneously, consequently reducing heat transfer problems.…”
Section: Introductionmentioning
confidence: 99%
“…2011). Araştırmacılar, doğal boyarmaddelerin uygulamalarına ait ultrasonik enerji, mikrodalga enerjisi ve süperkritik karbondioksit ile boyama gibi birçok yeni yöntem geliştirmişlerdir (Vankar ve Shanker,2006;Elshemy 2011;Liu ve ark. 2018;Shahid ve ark.…”
Section: Introductionunclassified